Training needs of art education teachers In light of the discipline-Based art education(Field study at primary schools in Tartous city) (Journal of Hama University, 2025)
The research aims to identify the degree of training needs of  art education teachers in the light of the discipline-Based art education according to their perspective and  the note card, as well as explore whether there are differences between the averages of teachers' scores in degree of training needs according to the variables ( educational experience, training courses) .To achieve the research , The descriptive approach was used and the sample consisted to (86) teachers in Tartus city. The researcher has prepared a questionnaire and note card to measure the degree of training needs of  art education teachers In light of the discipline-Based art education. consisting of (38) items, and distributed on four axes: (art history, art production, art criticism, aesthetics).The research reached several results.The degree of Needs of an art teachers in light of the discipline-Based art education from the teacher's point of view is moderate.- The degree of Needs of an art teachers in light of the discipline-Based art education According to the note card  is moderate.There are no statistically significant differences between the averages of the sample members’ answers about their training needs in light of the discipline-Based art education according to ( educational experience, training courses)  Key words: Training needs  _ the discipline-Based art education  _ Art education teachers
Keywords: Key words: Training needs _ the discipline-Based art education _ Art education teachers